The role of phosphatidylinositol-transfer proteins at membrane contact sites. (11th April 2016) - Selitrennik, Michael; Lev, Sima
Abstract : Phosphatidylinositol-transfer proteins (PITPs) have been initially identified as soluble factors that accelerate the monomeric exchange of either phosphatidylinositol (PI) or phosphatidylcholine (PC) between membrane bilayers in vitro . They are highly conserved in eukaryotes and have been implicated in different cellular processes, including vesicular trafficking, signal transduction, and lipid metabolism. Recent studies suggest that PITPs function at membrane contact sites (MCSs) to facilitate the transport of PI from its synthesis site at the endoplasmic reticulum (ER) to various membrane compartments. In this review, we describe the underlying mechanism of PITPs targeting to MCSs, discuss their cellular roles and potential mode of action.